Landscape visualization, sea-level change, and human occupation in Wādī Debayān, north-western Qatar - Tetlow, Emma; Cuttler, Richard; Al-Naimi, Faisal; Sheharyer, Ali; Bouhali, Othmane; Delaney, Liam; Adcock, James (Proceedings of the Seminar for Arabian Studies, 2013)
In December 2011 the Qatar National Historic Environment Record (QNHER), Qatar Museum Authority, and University of Birmingham, collaborated with Texas A&M University-Qatar (TAMUQ) to visualize sea-level change and its effects on patterns of human occupation on a site-specific level. These data were derived from extensive coring and subsurface modelling in Wādī Debayān, north-western Qatar. During prehistory, the wadi would have been subject to dynamic periods of environmental change. This has been related to two periods of dramatic sea-level rise during the Holocene geological epoch (12,000 BP to the present era). Evidence from other sites in Qatar indicates that these two episodes may have reached ’highstands’ of between 1 and 3 m above modern sea level. Visualizing the prehistoric environment of the wadi presents an important opportunity to test several assumptions about past environments and contributes to ongoing research aims. Immersive visualization allows the examination of the dramatic effects that dynamic environmental change would have had on past populations and prehistoric environments in the Arabian Gulf. This tool not only has applications for academic research but also for providing easy public access to archaeological and palaeoenvironmental research. There are important benefits for schools, universities, and museums, where visual representation can convey concepts more readily than descriptive narrative.